The Influence of Genetic and Environmental Factors and Their Interactions on Immune Response to Helminth Infections - Oyesola, Oyebola O.; Souza, Camila Oliveira Silva; Loke, P’ng (Frontiers in Immunology, 2022)
Helminth infection currently affect over 2 billion people worldwide, with those with the most pathologies and morbidities, living in regions with unequal and disproportionate access to effective healthcare solutions. Host genetics and environmental factors play critical roles in modulating and regulating immune responses following exposure to various pathogens and insults. However, the interplay of environment and genetic factors in influencing who gets infected and the establishment, persistence, and clearance of helminth parasites remains unclear. Inbred strains of mice have long been used to investigate the role of host genetic factors on pathogenesis and resistance to helminth infection in a laboratory setting. This review will discuss the use of ecological and environmental mouse models to study helminth infections and how this could be used in combination with host genetic variation to explore the relative contribution of these factors in influencing immune response to helminth infections. Improved understanding of interactions between genetics and the environment to helminth immune responses would be important for efforts to identify and develop new prophylactic and therapeutic options for the management of helminth infections and their pathogenesis.